Analysis of The Merdeka Belajar Kampus Merdeka (MBKM) Program on Improving Student Quality: A Systematic Literature Review - Dedi Prestiadi; Burhanuddin Burhanuddin; Raden Bambang Sumarsono (International Research-Based Education Journal, 2024)
MBKM activities have been carried out by many universities in Indonesia. Through MBKM activities, it is hoped that the quality of students will increase following the experience gained from the programs. This study aims to examine MBKM policies on student quality. This research method was carried out through the Literature Review (SLR) Study with the steps of this SLR research activity using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) which refers to four steps, namely Identification, Screening, Eligibility, and Included.. The result of this research is that MBKM activities can influence the improvement of student quality such as skills and direct experience to students.